Protein Tyrosine Phosphatase PRL2 Mediates Notch and Kit Signals in Early T Cell Progenitors. (19th January 2017) - Kobayashi, Michihiro; Nabinger, Sarah C.; Bai, Yunpeng; Yoshimoto, Momoko; Gao, Rui; Chen, Sisi; Yao, Chonghua; Dong, Yuanshu; Zhang, Lujuan; Rodriguez, Sonia; Yashiro‐Ohtani, Yumi; Pear, Warren S.; et al.
Abstract: The molecular pathways regulating lymphoid priming, fate, and development of multipotent bone marrow hematopoietic stem and progenitor cells (HSPCs) that continuously feed thymic progenitors remain largely unknown. While Notch signal is indispensable for T cell specification and differentiation, the downstream effectors are not well understood. PRL2, a protein tyrosine phosphatase that regulates hematopoietic stem cell proliferation and self‐renewal, is highly expressed in murine thymocyte progenitors. Here we demonstrate that protein tyrosine phosphatase PRL2 and receptor tyrosine kinase c‐Kit are critical downstream targets and effectors of the canonical Notch/RBPJ pathway in early T cell progenitors. While PRL2 deficiency resulted in moderate defects of thymopoiesis in the steady state, de novo generation of T cells from Prl2 null hematopoietic stem cells was significantly reduced following transplantation. Prl2 null HSPCs also showed impaired T cell differentiation in vitro. We found that Notch/RBPJ signaling upregulated PRL2 as well as c‐Kit expression in T cell progenitors. Further, PRL2 sustains Notch‐mediated c‐Kit expression and enhances stem cell factor/c‐Kit signaling in T cell progenitors, promoting effective DN1‐DN2 transition. Thus, we have identified a critical role for PRL2 phosphatase in mediating Notch and c‐Kit signals in early T cell progenitors. Stem Cells 2017;35:1053–1064 Abstract : Cooperation of PRL2 phosphatase with Notch and c‐Kit signals is critical for early T cell differentiation. Delta/Notch engagement induces the expression of both c‐Kit and PRL2 in ETPs. PRL2 then sustains and/or potentiates Kit signaling to facilitate DN1‐DN2 transition. In the absence of PRL2, c‐Kit expression is decreased and decreased c‐Kit expression promotes ETP differentiation toward myeloid lineages. Thus, sustaining high level of c‐Kit expression by PRL2 is crucial for ETP expansion, survival, and commitment during early stage T cell development.